7 Pemberdayaan Pemuda dalam Kegiatan Sosial Masyarakat (Football Championship RW 04 dan RW 18 Desa Mukapayung) - Cecep Carmedi, Ahmad Arifin Alghozali; Salma Putri Ardelia; Rian Febrian (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Youth are often considered an important asset in community development because of their potential to bring about positive change. Youth, as valuable assets for the future, have great potential to play a role in the positive transformation of society through active participation in various activity initiatives. This research discusses youth empowerment in community social activities as one of the important approaches in advancing the development and strengthening of community social values. The research shows that youth involved in empowerment activities have the opportunity to develop skills, increase understanding of social issues, and contribute actively in projects that benefit their neighborhoods. In addition, they also feel an increased sense of social responsibility and involvement in decision-making that impacts the social life of the community. Keyword : Community Social Activities, Youth, Football Championship.